Differentiating Through USP: Strategi Komunikasi Digital pada Akun Instagram @adiandfriendsorganizer - Amelia, Dhea; Pandrianto, Nigar (Kiwari, 2025)
Instagram has become a primary strategy for companies in reaching audiences, so that product or service promotion activities can be carried out effectively and efficiently. This study aims to analyze the application of content based on unique selling point (USP) as a marketing communication strategy to win the marketing competition in the Wedding Organizer industry, with a case study on the Instagram account @adiandfriendsorganizer. The research uses a qualitative approach with a case study research method. Data collection in this study involves in-depth interviews, non-participatory observation, document analysis, and literature study. The research focuses on analyzing the strategy of content on the @adiandfriendsorganizer Instagram account and how Adi & Friends Wedding Organizer communicates its USP through consistent content marketing to attract audience attention. The result show that the use of USP in each piece of content posted on Adi & Friends Instagram is highly effective in strengthening brand identity and increasing audience engagement. Through a communication strategy that consistently uses USP-based content, Adi & Friends Wedding Organizer has successfully built a stronger market position, enhanced customer loyalty, and gained a competitive advantage in the increasingly tight competition. Instagram menjadi strategi utama bagi perusahaan dalam menjangkau audiens, sehingga aktivitas promosi produk atau jasa dapat dilakukan secara efektif dan efisien. Penelitian ini bertujuan untuk menganalisis penerapan konten berbasis unique selling pointsebagai strategi komunikasi pemasaran dalam memenangkan persaingan pemasaran di industri wedding organizer, dengan studi kasus pada akun Instagram @adiandfriendsorganizer. Penelitian ini menggunakan pendekatan kualitatif dengan metode penelitian studi kasus. Pengumpulan data dalam penelitian ini menggunakan wawancara mendalam, observasi non-partisipatif, dokumen analisis serta studi kepustakaan. Dengan menganalisis strategi konten di Instagram Adi & Friends serta berfokus pada cara Adi & Friends Wedding Organizer dalam mengkomunikasikan unique selling point melalui konten marketing yang konsisten untuk menarik perhatian audiens. Hasil penelitian menunjukkan bahwa penggunaan USP dalam setiap konten yang diunggah di Instagram @adiandfriendsorganizer sangat efektif dalam memperkuat identitas merek dan membangun keterlibatan audiens yang lebih tinggi. Dengan strategi komunikasi menggunakan konten berbasis USP yang dilakukan secara konsisten, Adi & Friends Wedding Organizer berhasil membangun posisi yang lebih kuat di pasar, memperkuat loyalitas pelanggan dan memperoleh keunggulan yang kompetitif dalam menghadapi persaingan yang semakin ketat.